2014
DOI: 10.15376/biores.9.1.1334-1345
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Selective Acid Hydrolysis of Cellulose for Microcrystalline Cellulose using FeCl3

Abstract: In the process of acid hydrolysis of cellulose, hydrolyzing the amorphous regions while retaining the crystalline regions is the key technology for obtaining microcrystalline cellulose products. This paper investigated the influence of FeCl 3 on selective acid hydrolysis of crystalline regions and amorphous regions of cellulose. X-ray diffraction data indicated that FeCl 3 can enhance the selectivity of acid hydrolysis for amorphous regions of cellulose, thus improving the crystallinity of hydrocellulose. Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 12 publications
2
14
0
Order By: Relevance
“…2a). Generally, this result agreed with a previous study in which increased reaction temperature and acid concentration increased the crystallinity index (Li et al 2014). Therefore, the reaction conditions must be controlled in order to prevent overdegradation of cellulose into undesirable products.…”
Section: Effect Of Hydrolysis Variables By Rsm Optimization Studysupporting
confidence: 91%
See 1 more Smart Citation
“…2a). Generally, this result agreed with a previous study in which increased reaction temperature and acid concentration increased the crystallinity index (Li et al 2014). Therefore, the reaction conditions must be controlled in order to prevent overdegradation of cellulose into undesirable products.…”
Section: Effect Of Hydrolysis Variables By Rsm Optimization Studysupporting
confidence: 91%
“…It was observed that the CV value for the models of crystallinity index and nanocellulose yield was 5.09 and 2.06, respectively, which implied that there was a high degree of precision and a good deal of reliability of the experimental values in the reaction models. Moreover, the small value of standard deviation (SD) for both responses (y1 and y2) at 3.94 and 1.73, respectively, indicated good precision, reproducibility, and reliability of the experimental models (Li et al 2014). The precision of the model reflects the signal-to-noise ratio, and a value larger than 4 is normally desirable .…”
Section: Model Selection and Statistical Analysismentioning
confidence: 99%
“…showed a similar acid hydrolysis mechanism as inorganic acid (H2SO4) during the depolymerization of cellulose. The metal ions (Cr 3+ and Mn 2+ ) were generated from transition metal salts capable of attaching to the high electronegativity of oxygen atoms in β-1,4-glycosidic bonds of the cellulose chain, which resulted in weakening of the bond strength between pyranose rings in the amorphous region and thus led to the easy rupture of the cellulose chain into smaller fiber fragments (Li et al 2014a). Compared with single-charge protons (+1) from typical mineral acids (e.g., HCl or H2SO4), transition metal ions with higher valence states (e.g., +2, +3) can efficiently hydrolytically cleave the extensive network in the cellulose fibers.…”
Section: Morphological Study (Afm Analysis)mentioning
confidence: 99%
“…Amorphous part of the glycosidic bond partially degraded to form an acid insoluble nature of the final product, while the crystalline leaves a residue and only a change slightly due to acid hydrolysis. A slight change in the structure of the crystalline portion cellulose microcrystalline and amorphous parts will result in removal an increase in the degree of crystallinity of the microcrystalline cellulose [23]. Karim et al [24] reported for the treated sample, the disordered amorphous region was decreased with the increase of the hydrogen bond crystalline region of the cellulosic matrix, which might be due to the partial breaking up of glycoside linkages inside the amorphous region, whereas the crystalline region was almost unaltered [8].…”
Section: Resultsmentioning
confidence: 99%